Frequency of Seropositivity and Occupational Risks of HBV Infection in a Teaching Hospital in Bangladesh - Sarkar, Devendra Nath; Hossain, Md. Ismail; Shaheduzzaman, AKM; Ahmed, Mainuddinin; Amin, Robed (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 24 No 1, 2013, Page 20-24 DOI: http://dx.doi.org/10.3329/bjmed.v24i1.15031